Development of Innovation Management Strategies and Success of Thai Dessert Business in Central Region of Thailand - Limlahapun, Narumol; Kanchanathaveekul, Kanyamon (ABAC ODI JOURNAL Vision. Action. Outcome, 2019)
This study aimed to determine the features of Thai dessert business, features of innovation management strategy, and find an innovation management strategy development and the success of Thai dessert business in Central Region of Thailand. This study is a qualitative research where data collection was done by in-depth interview with key informants from Thai dessert entrepreneurs , using random sampling . The Thai dessert entrepreneurs selected were three types: Exporters, Entrepreneurs who have won in the entrepreneur community enterprises, Franchisees of Thai dessert business in four provinceswith a total of 90 persons selected. Twelve persons in the group of commercial academicians or specialists in Thai dessert business were selected. Data was analyzed using content analysis. The results indicated that various Thai dessert business were incorporated to the exporters, entrepreneurs who have won in the entrepreneur community enterprises, Franchisees of Thai dessert business used innovation management strategy such as marketing innovation like 1) segmentation of target market to achieve the most growth, 2) product improvement, 3) to increase the value of a current product or create something brand new. Exporters of Thai dessert business used the growth strategy, the entrepreneur community enterprises used the product development strategy and the franchisees of Thai dessert business focused on product identity enhancement. Innovation management strategy development of Thai dessert focused on marketing communication management of the brand using innovative communication technology from channels to match the target group of the product and to be clear, distinctive, different from other brands to remember that is in the mind of the buyer or the target customer. The process of marketing management, for example, tells the history of each Thai dessert to consumers, the value of Thai desserts on packaging, quality raw materials are procured from local distributors, businesses are expanding in franchise style and export. This will optimize competitiveness of Thai dessert business. The research found that the business had increased continuously, the company has the most inventive products on the market, and a network of the franchise.